Sustainable intensification of UK agriculture: concepts and application - Nunns, John (2022)
Sustainable intensification is a goal for 21st century agriculture that requires producing more food with less damaging outputs, including greenhouse gas emissions. This research observes the relationship between the inputs, practices and characteristics of cereal farms and the outputs produced. The activities of 336 cereal classified farms from the 2017 Farm Business survey were analysed using linear regression. Data on commercial outputs were taken directly from the survey. Greenhouse gas output data was derived using the Sustainable Intensification research Platforms carbon equivalency coefficients. Data on activity expenses and survey questions on specific techniques were used to observe practices. Farm location codes were used to observe the locational characteristics. Data collected by the University of Nottingham, on Land Grade Classifications, were used to add further detail to the locational characteristics. Analyses were performed at three different levels: total farm level output, per hectare output and per tonne output. At each level of measurement higher inputs generally led to higher outputs. Data on the specific techniques of green manure usage and precision farming proved to be significant. The former of these reduced emissions and the latter increased them, but also increased yields. This is despite both methods purporting to reduce emissions. These were only observable at a per hectare and per tonne level. Inputting data on location and on farm characteristics provided limited results. This showcased the limitations with the chosen carbon equivalency calculator and correlated with other studies using the same one. Although limitations were observed with the dataset, coefficient and with the scope of the research, it was found that similar methods could be used by policymakers to analyse trends in greenhouse gas mitigation and for individual farmers to improve resource use efficiency.